Effect of adding different levels of ginger powder diet on productive performance of Rose broiler - Rashid mousa, Ghassan; Kadhim Shakeer, Hayder (Journal of Kerbala for Agricultural Sciences, 2017)
This research was conducted in the field of domesticated birds in the Department of Animal Production techniques / Musayyib Technical College about the effect of adding different levels of ginger powder to feed on some productive traits of broiler chickens Rose during the period from 25/03/2016 up to 05/05/2016 using 250 sheet of smolts meat Rose strain-old one-day non-naturalized Ashaaiaa that have been distributed to five transactions (50 birds per treatment) and solving treated by any two frequencies (5 birds each repeater)Experiment included five transactions: Treatment first T1: fed a control diet without any additions. The second transaction T2: add them (0.5%) of ginger powder to a normal diet. Third treatment T3: add them (1%) of ginger powder to a normal diet. Fourth T4 treatment: add them (1.5%) of ginger powder to a normal diet. Treatment five o'clock T5: add them (2%) of ginger powder to a normal diet. Results indicate that T5 treatment showed (2%) significant superiority on all transactions and transactions (T4, T3, T2) in turn outperformed the moral control treatment T1 in the rate of body weight.As well as the treatment T5 outperformed the rest of the transactions, while T4 treatment outperformed the transactions T3, T2 and which in turn Tvoukta the control treatment to increase the weight cumulative. Feed consumption: moral differences did not appear at the age of 4 weeks between transactions from time T1 control treatment showed a significant increase in feed consumption on the rest of the transaction as well as the treatment T2 showed a significant increase in feed consumption on transactions (T5, T4, T3). For feed conversion coefficient excelled T5 treatment at all Alpmaamlat outperformed the place of transaction (T4, T3, T2) my game control treatment. The ratio of Almaah Hlakat: transactions showed the T2 - T5 significant decrease (P <0.05) in the percentage of Hlakat compared with the control treatment. Alncesph Almaah for Tsafa: outperformed all transactions of T5-T2 in the ratio of Almaah Tsafa the control treatment.